Pengaruh Book Tax Difference dan Volatilitas Penjualan Terhadap Persistensi Laba - Farah Fauziah; Dirvi Surya Abbas; Imas Kismanah (Akuntansi, 2023)
This research aims to determine the effect of Book Tax Difference, Sales Volatility on Profit Persistence. This research uses a sample of food and beverage companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The data used in this research is secondary data. The data obtained and collected is then processed using the EViews 12 application.